Potential Drug-Drug Interactions and Gender-Based Comparative Analysis of Chemotherapy-Related Side Effects in Oncology Patients: A Prospective, Comparative Study at a Tertiary Care Hospital in Urban India - Tuse, Trupti; Surve, Rahul; Gosavi, Ketakee; Ghanchi, Khushal Madanlal; Singh, Tarun (Indian Journal of Pharmacy Practice)
Background: Cancer patients often receive multiple medications, leading to Potential Drug-Drug Interactions (pDDIs) that may affect treatment outcomes. Chemotherapy-related side effects may also vary between genders, necessitating an understanding of these variations to improve patient care. Materials and Methods: This prospective, comparative study was conducted over 8 months (September 2023 to March 2024) at a tertiary care hospital in Urban India. A total of 273 patients were analysed for pDDIs and 213 patients were assessed for chemotherapy-related side effects. Patient data were collected using a structured data collection form. Drug interactions were assessed using Lexicomp® Solutions and data were analysed using SQL software. Statistical analysis, including chi-square tests, was performed using Microsoft Excel, with p-values < 0.05 considered statistically significant. Results: A total of 506 Potential Drug-Drug Interactions (pDDIs) were identified, with 88.2% of females and 90.3% of males experiencing at least one interaction. Pharmacodynamic interactions were more common (304 cases) compared to pharmacokinetic interactions (202 cases). The most frequent interaction was Aprecap-Dexa (11.06%), followed by Carboplatin-Paclitaxel (8.3%). Side effects were more prevalent in females, especially haematological side effects such as neutropenia (69% in females vs. 65.7% in males) and thrombocytopenia (24.6% in females vs. 23.28% in males). Non-haematological side effects, including indigestion and acidity, were also higher in females compared to males. Conclusion: This study highlights a high prevalence of pDDIs in oncology patients, emphasizing the need for proactive monitoring and clinical pharmacist involvement. Gender-specific differences in chemotherapy side effects suggest the need for personalized supportive care interventions to optimize treatment outcomes.
Keywords: Anti-Cancer Therapy; Drug-Drug Interactions (DDIs); Gender Differences; Side Effects